Reforming the Syariah Studies in Malaysian Higher Learning Institution - Abd Rahim, R.A.; Man, Saadan (2011)

(untitled)
With the coming of modern time signified by the globalization, the present Malaysian Higher Education Ministry had initiated various reforms to provide the Malay-Muslim society with the competent and modern educational system. In this article we will demonstrate such reformation program by focusing upon the Syariah studies in the University of Malaya. This paper is designed to be divided into several sections. First, is about Islamic resurgence in Malaysia and its impact upon the present government educational policies. Second, the Malaysian’s government policies towards reforming the higher learning institution. Third, the concept of Syariah studies in Islam followed by the introduction of Academy of Islamic Studies in University of Malaya and its reform program, which will emphasize on the use of new curriculum as well as pedagogical approaches. Among such approaches are the introduction of the contemporary concept of Islamic law, adopting the Problem Based Learning (PBL) method, E-Learning technologies and implementation of the THE (Times Higher Education) standard of ranking in assessing the quality of Syariah studies in University of Malaya. Fourth, the conclusion followed by several suggestions for the betterment of Syariah studies in Malaysia.